A leader-followers model of transmission augmentation for considering strategic behaviours of generating companies in energy markets - Hesamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (Elsevier, 2009)
This paper suggests an integrated mathematical framework developed based on the leader-followers game for augmentation of transmission networks. Transmission Network Service Provider moves first and designs the horizon year transmission system. Generating Companies compete for having the highest share from the energy market and they find their equilibrium point using the Nash equilibrium concept. Finally, Market Management Company receives the planning schedule of transmission system and the energy offer prices and clears the market. In addition to the exact mathematical modelling of the interested players of transmission planning problem, the methodology can design the future transmission system not only for improving the system social welfare but also for encouraging competition among horizon year generating companies.